Working Conditions and Work-related Injuries and Illnesses on board Norwegian Floating Factories after World War II - Wexelsen, Einar (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Sørishavet; arbeidsforhold; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; medisin

Krill Enzymes. A New Concept for Efficient Debridement of Necrotic Ulcers - Hellgren, L.; Karlstam, B.; Mohr, Viggo; Vincent, J. (International Journal of Dermatology, 1991)
The article discusses the new concept for surgery of necrotic ulcers using the krill enzymes. The krill peptide hydrolases represent a new and important alternative to mammalian or microbial enzymes for distinctive medical applications, such as debridemen.
Keywords: Sørishavet; biokjemi; krill; marin biologi; medisin; plankton

Medical contingency and biomedical research - Molvær, Otto Inge; Bendiksen, Fredrik S; Reitehaug, Per-Ivar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; biomedisin; medisin